Pengembangan Bahan Ajar Audio Visual Berbentuk Video dengan Menggunakan Aplikasi Canva dalam Pembelajaran PAI - Saizul, Alfira; Razali Abdullah, Khadijah; Wardhani, Nia (Pase: Journal of Contemporary Islamic Education, 2023)
Abstract: This study aims to describe the develop of audio-visual based learning media (video) through Canva Application in PAI learning. The design of this study is library research. Based on descriptive and textual analysis refer to primary data is teaching material, secondary datais teachers and students and another data sources to support the study of the research. The result finding is the used of audio visual through Canva Application to increase students learning motivation on the material and the used of audio-visual learning media (video) is basically intended to make learning activities more effective in learning goals can be achieved well. Keyword: Teaching Materials Innovation, Audio-visual Videos, Canva Application